The Influence of Polyhexamethylene Guanidine Derivatives Introduced into Polyhydroxybutyrate on Biofilm Formation and the Activity of Bacterial Enzymes - Brzezinska, M. Swiontek; Walczak, M.; Richert, A.; Kalwasinska, A.; Pejchalová, Marcela (MAIK Nauka/Interperiodica/Springer, 2016)
Escherichia coli and Staphylococcus aureus were able to produce biofilm on the surface of polyhydroxybutyrate (PHB), but their abundance depended on type and the concentrations of the polyhexamethylene guanidine (PHMG) derivatives introduced in PHB. Different types of PHMG derivatives inhibited S. aureus ATCC 6538P biofilm formation, but PHB with PHMG salt of sulfanilic acid stimulated E. coli ATCC 8739 biofilm formation. The presence of all PHMG derivatives decreased significantly the number of viable cells of the test bacteria directly proportional to the concentration of the biocidal agent. PHMG derivatives affected the activity of microbiological hydrolases with different degrees. Some of them (PHB with PHMG stearate) stimulated activity of E. coli ATCC 8739 hydrolases, other (PHB with the PHMG salt of sulfanilic acid) inhibited activity of the S. aureus ATCC 6538P hydrolases. The PHMG derivatives introduced in PHB also inhibited the activity of bacterial dehydrogenases
Vliv derivátů polyhexamethylen guanidinu zakomponovaných do Polyhydroxybutyrátu na tvorbu biofilmu a aktivitu bakteriálních enzymů
Keywords: polyhydroxybutyrate; biofilm; bacterial enzymes; poyhyroxybutarát; biofilm; bakteriální enzymy